Pengaruh Perceived Incentives Terhadap Purchase Intention Of Electric Vehicle Melalui Perceived Usefulness Di Indonesia - Lesmana, Cep Sunandar; Dewi, Citra Kusuma (eProceedings of Management, 2024)
Air pollution is a serious issue and a prevalent phenomenon in Indonesia, with harmful impacts on public health andthe environment. Currently, the Indonesian government is strongly committed to achieving Net Zero Emission (NZE)by 2060. Net zero emissions (NZE) means that the amount of carbon emissions released into the atmosphere does notexceed the amount that can be absorbed by the Earth. The objective of this research is to explore the influence ofPerceived Incentives, Perceived Usefulness, and Purchase Intention concerning electric vehicles in Indonesia. Thisstudy adopts a descriptive and quantitative approach. Non-probability sampling, specifically purposive sampling, wasutilized to select respondents who are knowledgeable and interested in electric vehicles in Indonesia. The researchersemployed Likert scales for measurement, targeting an unspecified population size. The study involved 273 respondentsand utilized SmartPLS version 3.0 for data analysis. Based on the processed data, it was found that PerceivedIncentives have a positive influence on Perceived Usefulness. Perceived Usefulness, in turn, positively affects thePurchase Intention of Electric Vehicles. Furthermore, Perceived Incentives significantly influence the PurchaseIntention of Electric Vehicles directly and also indirectly through Perceived Usefulness.Keywords-percived incentives, percived usefulness, purchase intention